PERSEPSI MAHASISWA TERHADAP PELAKSANAAN PERKULIAHAN DAN HUBUNGANNYA DENGAN PARTISIPASI MAHASISWA DALAM PERKULIAHAN (Studi Tentang Mahasiswa Semester Genap Jurusan Sosiologi Universitas Riau) - Mukhtar "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in a Department Sociology University RiauPekanbaru. With a problem that (1) what is the student’s perception of thephysical condition of the class, the learning materials and the process or the wayof delivery of learning materials ? (2) how to participate in the lectures ? (3) howis the relationship between student’s perceptions of the physical condition of theclass, learning materials and the process or manner of delivery of learningmaterials with the participation of students in lectures ?. the purpose of thisresearch was, to determine how student’s perceptions of the physical condition ofthe class, the learning materials, and the process or the way of delivery oflearning materials, to determine how to participate in the lectures, and todetermine how is is the relationship between student’s perceptions of the physicalcondition of the class, the learning materials, and the process or manner ofdelivery of learning materials, with the participation of student’s in lectures. Theresearch is descriptive research with quantitative approach, the population of thisresearch much as 615 people, then used one of the sampling technique fromsimple random sampling, then got a sample of 38 people the forch of 2014, 38people from the force of 2015, and 47 people from the force of 2016, to collectthis research data used questionnaires and documentation. Based on the result ofthe research, (1) it can be concluded that from 123 respondents with percentageof 81,3 % positive perception on lecturing, and 23 respondents with percentage of18,7 % have negative perception toward lecturing activity (2) from 123respondents there are 109 respondents with percentage 88,6 % participated highand 14 respondents with percentage 11,4 % participated in low lecture (3) therelationship between student perception toward lecturing with studentparticipation in lecture equal to 0,747 (74,7 %) strong relation, hence can bestated that ha accepted meaning the relationship between students peceptions oflecturing with student participation in lectures and relationship is strong.Keywords : lecturing, perception, participation